Efeito do adubo verde e época de semeadura sobre a produtividade do feijão, em plantio direto em região de cerrado - Simidu, Helena Masumi [UNESP]; Sá, Marco Eustáquio de [UNESP]; Souza, Lilian Christian Domingues de [UNESP]; Abrantes, Fabiana Lima [UNESP]; Silva, Mariana Pina da [UNESP]; Arf, Orivaldo [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2010)
Effect of green manure and sowing date on the productivity of bean no-tillage in the Cerrado region. Green manure and sowing date are two important factors that influence the productivity of cultivars. The objective of this study was to evaluate the production of biomass from different vegetation covers (millet, sorghum and Brachiaria brizantha) and the accumulation of nutrients and their effects on the bean cultivars (Pearl, IAC Tuna and Carioca Precoce) at different sowing dates (6/22 and 7/6). The experiment was conducted at the experimental area of the Universidade Estadual Paulista - Unesp, located in Selviria, Mato Grosso do Sul State, in the 2006/2007 agricultural year. The randomized blocks design was used with four replications, and the evaluations of the coverage were: the biomass of fresh and dry matter and nutrients accumulated in plants; for the beans: cycle, final stand, number of pods/plant, number of seeds per pod, mass of 100 seeds, and productivity. It was observed that millet and sorghum showed higher productivity of fresh and dry mass, and accumulate greater quantity of nutrients in straw; the time most suitable for sowing was in June, and the late sowing of cv. Carioca Precoce did not affect their productivity, the use of Brachiaria brizantha straw in coverage provided better conditions for productivity in the bean no-tillage system.
Effect of green manure and sowing date on the productivity of bean no-tillage in the Cerrado region.
Keywords: green fertilizer; no-tillage; planting times; bean cultivars